The product in simplest form is (x - 4)
<em><u>Solution:</u></em>
<em><u>Given expression is:</u></em>
We have to find the product in simplest form
In the given expression,
2x + 8 = 2(x+ 4)
We know that,
Therefore,
Substitute these in given expression
Cancel the common factors,
Thus the product in simplest form is (x - 4)
Answer:
- (4x -4)° +x° +(6x-3)° = 180°
- J = 99°
- K = 64°
- L = 17°
Step-by-step explanation:
The relation that helps you write an equation for x is, "the sum of angles in a triangle is 180°."
__
<h3>equation</h3>
(4x -4)° +x° +(6x -3)° = 180° . . . . . sum of angles in this triangle
<h3>solution for x</h3>
11x -7 = 180 . . . . . . . divide by °, collect terms
11x = 187 . . . . . . . . add 7
x = 17 . . . . . . . . . divide by 11
<h3>angle values</h3>
m∠J = (6x -3)° = (6(17) -3)° = 99°
m∠K = (4x -4)° = (4(17) -4)° = 64°
m∠L = x° = 17°
Hello here is a solution :
Step-by-step explanation:
I am not critically certain but the ways you have jotted down your enquiry..
<h2>I assume is</h2>
13 × (4×11)
13 × 44
=572 - 44= 528
528+13 =541
541 ×13=7033
Answer:
f(x)= x^2 - 2, the one in red.
Step-by-step explanation:
To move a quadratic function up/down, you change the value at the very end of the formula.
So instead of f(x)= x^2 + 1, you would do f(x)= x^2 - 2, to move it down 3. This would be the one in red.